Implementation of a Random Variable Universefuzzy Controller in Medical Helmet - WANGYue; ZHAOHui; ZHANGYuan; WULunhua (Journal of Harbin University of Science and Technology, 2023)
The current adaptive fuzzy control methods was difficult to achieve good results in practical problems. Aiming at this problem , a fuzzy controller with a random variation domain was proposed. Firstly , a simple and accurate random scaling factor was designed based on the original scaling factor , and its performance was verified by simulation comparison; Then , the error and error change of the expected value of the actual front and rear ring beam expansion and contraction and the length expectation of the front and rear ring beam expansion and contraction under ideal conditions are used as input variables , and the number of knob speed changes are used as the output variable , and the random variable domain Fuzzy controller was designed; Finally , the performance of the fuzzy controller of the design was significantly improved by comparing the response curve of the simulation experiment. And the entire control process is small , high stability , response time has been significantly shortened , to achieve the treatment effect of medical helmets.